DESAIN DAN IMPLEMENTASI SISTEM SMART HOME BERBASIS WI-FI - Arafat Arafat (AL-ULUM: JURNAL SAINS DAN TEKNOLOGI, 2017)
The rapid development of mobile communication technology advances and cost reductions possible to incorporate mobile technology into the smart home system. We proposed a system of mobile and internet-based smart home consisting of a mobile phone with android, Internet-based applications, and server blynk. Home appliances can be controlled by an Arduino that receives commands from the server computer, which operates in accordance with commands received from the mobile application via a wifi network or the internet. In the proposed system, a home server is made using Wi-Fi technology that receives order from clients and orders will be processed through the Arduino, which allows users to control and monitor all the parameters associated with home using Andriod smart phone or via the internet. This study present the design of a low cost innovative and automated control based on weather conditions, the control apparatus, and home security together with android application to allow smart phones to send commands using blynk. Keywords: Smart Home, Arduino UNO, Wi-Fi, blynk